2011
DOI: 10.4067/s0716-078x2011000300001
|View full text |Cite
|
Sign up to set email alerts
|

Fire regimen and spread of plants naturalized in central Chile

Abstract: Setting fi res is an old practice of land management in the Mediterranean region of central Chile. Fire in the region is currently of predominantly human origin and previously published material suggests that the scheduling of these activities is associated with the spread of naturalized exotic species. Research into the effects of fi re on both native and exotic Mediterranean vegetation in central Chile has increased notably over recent years. The objective of our review is to highlight new knowledge in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 17 publications
0
7
0
4
Order By: Relevance
“…Regarding the wildfire regime, Chile has a long history of manmade burning for land clearance and management (Armesto et al 2009;Contreras et al 2011). Most fires (44%) incinerate due to vehicular transport (e.g., cigarettes thrown out of the driving car), tourism activities (camp fires) (27%), and intentional arson (18%).…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the wildfire regime, Chile has a long history of manmade burning for land clearance and management (Armesto et al 2009;Contreras et al 2011). Most fires (44%) incinerate due to vehicular transport (e.g., cigarettes thrown out of the driving car), tourism activities (camp fires) (27%), and intentional arson (18%).…”
Section: Study Sitementioning
confidence: 99%
“…Central Chile is characterized by a Mediterranean climate and a transition zone between sclerophyllous and deciduous vegetation. While natural wildfires are not typical for the region, human-induced wildfires have become alarmingly more frequent during the last decades (Armesto et al 2009;Contreras et al 2011). McWethy et al (2018) have identified land-use change as an important driver of wildfire activity in Chile.…”
Section: Introductionmentioning
confidence: 99%
“…Para la Región de Valparaíso se han reportado en las laderas de solana hasta unas cincuenta especies alóctonas asilvestradas (Contreras et al 2011), muchas relacionadas con la regeneración de ambientes sometidos a incendios forestales; también, se ha señalado que las agrupaciones vegetales más ricas en especies se encuentran en las laderas de umbría (Redon 2003). Ambos resultados son similares a los registrados en este estudio.…”
Section: Familia Especie Fuenteunclassified
“…Accordingly, the degree of invasibility of an ecosystem can be increased by fire occurrence (Contreras et al . ; Mandle et al . ).…”
Section: Introductionmentioning
confidence: 99%